Determinants of Intention to Participate in Breast Cancer Screening among Urban Chinese Women: An Application of the Protection Motivation Theory - Miao Zhang (MDPI AG, 2021)
Despite the significance of early detection of breast cancer through screening, the screening uptake in China remains relatively low. Protection motivation theory (PMT) suggested by Rogers is one of the theories concerning threat appeal. This study aimed to apply the protection motivation theory (PMT) in predicting breast cancer screening intention. In this cross-sectional study, a sample of Chinese urban women was recruited using the convenient sampling method from five communities in Wuhan. Data were collected using a self-report questionnaire that included demographic variables, knowledge about breast cancer, six PMT subconstructs, and screening intention. We used the structural equation modeling (SEM) to identify the predictor factors associated with screening intention. Of the total sample (n = 412), 86.65% had intention to participate in screening. Our data fit the hypothesized SEM model well (Goodness of fit index (GFI) = 0.91, adjusted GFI (AGFI) = 0.89, comparative fit index (CFI) = 0.91, root mean square error of approximation (RMSEA) = 0.05, standardized root mean residual (SRMR) = 0.06, and Chi-square/df = 2.01). Three PMT subconstructs (perceived severity, response cost, and self-efficacy) were significantly associated with screening intention. Knowledge, social status, and medical history had significantly indirect associations with screening intention through the mediating effect of PMT subconstructs. Considering the utility of PMT, intervention programs might be more effective based on the subconstructs of PMT, especially to improve self-efficacy, perceived severity, and knowledge, reduce response cost, as well as targeting specific demographic groups.